MALFORMATIONS OF INTESTINE IN PREMATURE INFANTS UNDER THE MASK OF NECROTIZING ENTEROCOLITIS - Yu. I. Kucherov; Yu. V. Zhirkova; T. N. Shishkina; M. G. Rekhviashvili ("Paediatrician" Publishers LLC, 2015)
Some congenital malformations of the gastrointestinal tract in premature infants are difficult to diagnose due to a lack of specific clinical picture. As a rule, they are masked under necrotizing enterocolitis resulting in the improper management of such patients. The article describes two clinical cases of Hirschsprung's disease and neuronal intestinal dysplasia in newborns. Both cases were regarded as necrotizing enterocolitis of newborns resulting in tactical treatment errors. We made a conclusion that the surgical tactics for patients with congenital disorders of both the enteric nervous system and muscular intestinal wall tissue, which manifest themselves as enterocolitis or perforation, should be determined only when you are fully confident in the functional usefulness of all parts of the intestine.